Spectrum of hematological malignancies, clonal evolution and outcomes in 144 Mayo Clinic patients with germline predisposition syndromes. Issue 11 (27th August 2021) - Martin, Emma St; Ferrer, Alejandro; Mangaonkar, Abhishek A.; Khan, Shakila P.; Kohorst, Mira A.; Joshi, Avni Y.; Hogan, William J.; Olteanu, Horatiu; Moyer, Ann M.; Al‐Kali, Aref; Tefferi, Ayalew; Chen, Dong; et al.
Abstract: Germline predisposition syndromes (GPS) result from constitutional aberrations in tumor suppressive and homeostatic genes, increasing risk for neoplasia in affected kindred. In this study, we present clinical and genomic data on 144 Mayo Clinic patients with GPS; 59 evaluated prospectively using an algorithm‐based diagnostic approach in the setting of a dedicated GPS/ inherited bone marrow failure syndrome (IBMFS) clinic. Seventy‐two (50%) patients had IBMFS (telomere biology disorders‐32, Fanconi anemia‐18, Diamond Blackfan Anemia – 11, congenital neutropenia–5, Schwachman‐Diamond Syndrome‐5 and Bloom Syndrome‐1), 27 (19%) had GPS with antecedent thrombocytopenia ( RUNX1 ‐FPD‐15, ANKRD26 ‐6, ETV6 ‐2, GATA1 ‐1, MPL ‐3), 28 (19%) had GPS without antecedent thrombocytopenia ( GATA2 haploinsufficiency‐16, DDX41 ‐10, CBL ‐1 and CEBPA ‐1) and 17 (12%) had general cancer predisposition syndromes (ataxia telangiectasia‐7, heterozygous ATM variants‐3, CHEK2 ‐2, TP53 ‐2, CDK2NA ‐1, NF1 ‐1 and Nijmegen Breakage Syndrome‐1). Homozygous and heterozygous ATM pathogenic variants were exclusively associated with lymphoproliferative disorders (LPD), while DDX41 GPS was associated with LPD and myeloid neoplasms. The use of somatic NGS‐testing identified clonal evolution in GPS patients, with ASXL1, RAS pathway genes, SRSF2 and TET2 being most frequently mutated. Fifty‐two (91%) of 59 prospectively identified GPS patients had a change in their management approach, including additional GPS‐related screening in 42 (71%), referral for allogenic HSCT workup and screening of related donors in 16 (27%), medication initiation and selection of specific conditioning regimens in 14 (24%), and genetic counseling with specific intent of fertility preservation and preconceptual counseling in 10 (17%) patients; highlighting the importance of dedicated GPS screening, detection and management programs for patients with hematological neoplasms.